Composite Follicular Variant of Papillary Carcinoma and Mucoepidermoid Carcinoma of Thyroid Gland: A Case Report - Jung, Yong Han (The Korean Academy of Medical Sciences, 2010)
A 50-yr-old male presented a thyroid mass with dysphasia and hoarseness. He underwent total thyroidectomy and neck node dissection. Pathologically, the tumor had two distinct tumor components with intermingled areas: follicular variant of papillary carcinoma and mucoepidermoid carcinoma. Mucoepidermoid carcinoma composed of columnar cells, mucocytes, and squamoid cells showing solid and cystic lesion. Several small cysts lined by benign ciliated columnar epithelia suggesting that this tumor had originated from solid cell nest were seen around the tumor. By immunohistochemistry, columnar cells and squamoid cells in mucoepidermoid carcinoma were positive for cytokeratin but negative for thyroglobulin, TTF-1 and calcitonin. Positivity of p63 was seen in squamoid cells and basal cells of cysts. Some mucocytes are CEA positive. Tumor cells of papillary carcinoma are positive for TTF-1, thyroglobulin but negative for CEA, calcitonin and p63.